2022
DOI: 10.1038/s41598-022-06664-z
|View full text |Cite
|
Sign up to set email alerts
|

Sleep macro- and microstructure in breast cancer survivors

Abstract: Complaints of sleep disturbance are prevalent among breast cancer (BC) patients and are predictors of quality of life. Still, electrophysiological measures of sleep are missing in patients, which prevents from understanding the pathophysiological consequences of cancer and its past treatments. Using polysomnography, sleep can be investigated in terms of macro- (e.g. awakenings, sleep stages) and micro- (i.e. cortical activity) structure. We aimed to characterize sleep complaints, and macro- and microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…However, the negative associations with breast cancer remain unclear. Patients with breast cancer may suffer from REM or NREM sleep problems [25,26]. A previous study revealed that demoralization mediates the effect of stress on sleep disturbances in patients with breast cancer [18].…”
Section: Demoralization and Its Association With Quality Of Life Slee...mentioning
confidence: 99%
“…However, the negative associations with breast cancer remain unclear. Patients with breast cancer may suffer from REM or NREM sleep problems [25,26]. A previous study revealed that demoralization mediates the effect of stress on sleep disturbances in patients with breast cancer [18].…”
Section: Demoralization and Its Association With Quality Of Life Slee...mentioning
confidence: 99%
“…This indicates that sleep quality is a more distal factor influencing HRQOL, with sleep behavior related to personal plans and awareness, while depression and disability were more direct factors affecting HRQOL. The sleep disturbance model suggests that sleep disorders adversely affect physical health by weakening emotional regulation and disrupting the body’s circadian rhythm 45 . Hence, the impact of sleep quality on HRQOL is primarily mediated through an indirect pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although sleep disturbances are thought to be a side effect of cancer treatment, notably chemotherapy [ 13 , 83 ], multiple studies showed that sleep complaints in BC exist even in BC patients who did not receive chemotherapy [ 84 , 85 ] and their presence has detrimental effects on patients’ quality of life [ 86 ]. Sleep is intrinsically linked to circadian rhythms and a recent review highlighted the presence of circadian disruptions in BC, more specifically of cortisol and rest-activity rhythms [ 13 ].…”
Section: Discussionmentioning
confidence: 99%